Fast biofoundries: coping with the challenges of biomanufacturing. Issue 7 (July 2022) - Tellechea-Luzardo, Jonathan; Otero-Muras, Irene; Goñi-Moreno, Angel; Carbonell, Pablo
Abstract : Biofoundries are highly automated facilities that enable the rapid and efficient design, build, test, and learn cycle of biomanufacturing and engineering biology, which is applicable to both research and industrial production. However, developing a biofoundry platform can be expensive and time consuming. A biofoundry should grow organically, starting from a basic platform but with a vision for automation, equipment interoperability, and efficiency. By thinking about strategies early in the process through process planning, simulation, and optimization, bottlenecks can be identified and resolved. Here, we provide a survey of technological solutions in biofoundries and their advantages and limitations. We explore possible pathways towards the creation of a functional, early-phase biofoundry, and strategies towards long-term sustainability. Highlights: Laboratory automation is playing a crucial role in the development of synthetic biology methodologies, allowing fast and inexpensive engineering of genetic circuits for a wide range of biotechnological applications. Synthetic biology laboratories are in the midst of a paradigm shift, catalyzed by biofoundries and their new approach to engineering biology. The innovative, resource-intensive and risky nature of biofoundries demand informed decisions before committing to building a new facility.